Association between central sleep apnea and left ventricular structure: the Multi‐Ethnic Study of Atherosclerosis. (21st February 2017) - Javaheri, Sogol; Sharma, Ravi K.; Bluemke, David A.; Redline, Susan
Summary: We assessed whether the presence of central sleep apnea is associated with adverse left ventricular structural changes. We analysed 1412 participants from the Multi‐Ethnic Study of Atherosclerosis who underwent both overnight polysomnography and cardiac magnetic resonance imaging. Subjects had been recruited 10 years earlier when free of cardiovascular disease. Our main exposure is the presence of central sleep apnea as defined by central apnea–hypopnea index = 5 or the presence of Cheyne–Stokes breathing. Outcome variables were left ventricular mass/height, left ventricular ejection fraction, and left ventricular mass/volume ratio. Multivariate linear regression models adjusted for age, gender, race, waist circumference, tobacco use, hypertension, and the obstructive apnea–hypopnea index were fit for the outcomes. Of the 1412 participants, 27 (2%) individuals had central sleep apnea. After adjusting for covariates, the presence of central sleep apnea was significantly associated with elevated left ventricular mass/volume ratio ( β  = 0.11 ± 0.04 g mL −1, P  = 0.0071), an adverse cardiac finding signifying concentric remodelling.